THE EFFICACY OF PAPAYA LEAF EXTRACT INCLUSION IN DRINKING WATER AS AN IMPROVING OF LAYER QUAIL PRODUCTION - Kusbiyantari, Asri; Kardaya, Dede; Sudrajat, Deden (Universitas Djuanda Bogor, 2017)
Bacterial resistance to antibiotic has made the reduction in the use of antibiotic a concern in animal production. The restriction of antibiotic application in animal production can be achieved if the antimicrobial strategy is available. Papaya leaf extract has some antibacterial properties that make it is potential to be used as a substitute for commercial antibiotic. This study was aimed at assessing the efficacy and potential of papaya leaf extract inclusion in drinking water in controlling pathogenic bacteria and improving the production efficiency and feed conversion ratio (FCR) of layer quails. The study was conducted from 24 August to 20 September 2016 at the poultry farm of Department of Animal Husbandry, Djuanda University, Bogor. One-hundred layer quails were allocated into 4 treatments and 3 replicates in a completely randomized design. The treatments consisted of five levels of papaya leaf extract inclusions in drinking water , namely drinking water + commercial antibiotic of 0.5 g/liter water (R1), drinking water + papaya leaf extract of 10 ml/liter water (R2), drinking water + papaya leaf extract of 20 ml/liter water (R3), and drinking water + papaya leaf extract of 30 ml/liter water (R4). Data were subjected to an analysis of variance and a Duncan test. Results showed that the inclusion of papaya leaf extract in drinking water gave significant effects on egg mass, egg production efficiency, FCR, egg quality index, and egg shell thickness but not on feed intake, egg weight, and mortality rate. It was concluded that papaya leaf extract produced by a boiling method could be used as a substitute for synthetic antibiotic. Key words: Papaya leaf extract, production efficiency, feed conversion, layer quail.